Brave New Words: How AI Will Revolutionize Education (and Why That’s a Good Thing) - Rubia Shaukat (CISS Insight Journal, 2024)
Artificial Intelligence (AI) is transforming education and Salman Khan’s Brave New Words: How AI Will Revolutionize Education offers a compelling exploration of this shift. The book, organized into eight chapters, examines the role of AI—particularly Generative Pre-Trained Transformer (GPT) technology—in reshaping classrooms, personalizing learning, and addressing educational inequities. Written for educators, parents, and students, Khan blends practical advice with visionary predictions about how AI can fundamentally enhance teaching and learning experiences. Drawing on his experience as the founder and CEO of Khan Academy—a globally acclaimed online learning platform—Khan shares valuable insights and recounts his journey of integrating OpenAI’s advanced large language models (LLMs) into education. The book highlights the immense potential of AI to reshape teaching and learning in profound ways.As a prominent figure in Education Technology (EdTech), Salman Khan adopts a forward-thinking and optimistic perspective. Rather than approaching tools like ChatGPT with skepticism, he advocates for an open minded and proactive stance. He encourages parents and educators to embrace AI’s possibilities while acknowledging its imperfections. Khan demonstrates how AI can personalize learning, enhance assessments, and support classroom activities in innovative ways, complementing traditional educational methods to create more engaging and impactful learning experiences.